KONTRIBUSI PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAN INVESTASI DAERAH PEMERINTAH KOTA SURABAYA - Rosdiana, Novia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this researchis to find out effectiveness and efficiency of PAD in the city of Surabaya, effectiveness of regional spending, and Original Local Revenue PAD contribution to the regional spending also the growth of regional investment (PMDN) in the city of Surabaya. The research method used in this research is qualitative descriptive which were collected, analyzed, and interpreted data obtained so that is gives correct and complete information to solve the problem faced. The results of this study show that in the period of 2009 â 2012 PAD in the city of Surabaya has been increasing every years, it also follows with the increase of regional spending every years, but PAD contribution to the regional spending experienced up and down. The increase of PAD contribution to the regional spending happened in the year of 2011 â 2012. Meanwhile, PAD contribution to the regional investment(PMDN) also has been increasing every years, the most significant increase happened in 2012.Keywords: Original Local Revenue (PAD), Regional Spending, Local Capital Investment